The use of technology to protect the health of athletes during the heat of Tokyo - Angeloudis, K.; Muniz-Pardos, B.; Smeeton, N.; Guppy, F.; Pitsiladis, Y. (BASEM, 2020)
Tokyo will host the Summer Olympics from July 23rd to August 8th 2021, with averaged air temperatures surpassing 30oC and humidity levels above 70%[1]. Notably, forecasts indicate increments in the intensity and consistency of heatwaves globally because of environmental change[2]. In recent years there has been an increasing number of heat illness cases in Tokyo, with over 65 deaths recorded in only one week in August 2018[3]. Interestingly, daily air temperatures during the summer of 2020 have been remarkably low when contrasted with the past two years. Despite the fact that this is by all accounts an abnormal season characterised by a broadened rainy period, 2021 is expected to face more intense heat and humid conditions, based on the La Niña forecasting models (i.e., powerful winds moving the hot waters of the Pacific Ocean from South America towards Indonesia). These predictions point towards warm irregularities that could probably be present in Japan during June-August 2021[4].